2008
DOI: 10.2214/ajr.07.3032
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal and Dynamic Contrast-Enhanced MRI for Detection of Local Recurrence After Radical Prostatectomy

Abstract: MRI combined with dynamic contrast-enhanced MRI showed a higher sensitivity and specificity compared with MRI alone in detecting local recurrences after radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 29 publications
5
93
0
2
Order By: Relevance
“…Casciani et al [41] in a single centre retrospective study described the use of MRI with DCE in 46 patients previously submitted to RP and with biochemical recurrence. All patients were submitted to both endorectal MRI and DCE-MRI.…”
Section: Multiparametric Mrimentioning
confidence: 99%
“…Casciani et al [41] in a single centre retrospective study described the use of MRI with DCE in 46 patients previously submitted to RP and with biochemical recurrence. All patients were submitted to both endorectal MRI and DCE-MRI.…”
Section: Multiparametric Mrimentioning
confidence: 99%
“…A study of 70 patients at high risk of local recurrence after RP demonstrated that combined MRSI and DCE-MRI showed a high sensitivity and specificity in identifying local prostate cancer recurrence in patients with biochemical progression after RP [98] . A study of 51 patients concluded that MRI combined with DCE-MRI is an accurate method to identify local recurrence after radical prostatectomy [99] . A study concluded that prostate cancer local recurrence after radiation therapy occurs at the site of the primary tumor [100] .…”
Section: Tumor Recurrencementioning
confidence: 99%
“…16 MR imaging with endorectal coil, combined with dynamic contrast-enhanced imaging, seems to have a higher sensitivity and specificity compared with MR imaging alone in detecting local recurrences after RP. 17 The application of MR imaging and nuclear medicine (positron emission/CT (PET/CT) with new tracers like 11 C or 18 F-choline and acetate) might offer a better assessment of recurrent PCa. 18 The detection rate is directly correlated to the PSA value at the time of study, with detection rates between 36 and 60% at levels below 1 and a sensitivity of approximately 80% for values up to 2.5 ng ml À1 .…”
Section: Diagnostic Evaluationmentioning
confidence: 99%